Current topical trends and novel therapeutic approaches and delivery systems for oral mucositis management - Anmar Al-Taie; Athmar D Al-Shohani; Zahraa Albasry; Ataa Altaee (Wolters Kluwer Medknow Publications, 2020)
Oral mucositis (OM) is an extremely serious and challenging complication of chemoradiotherapy, which may limit the efficacy of cancer treatment. Complications related to OM include potential nutrition impairment, high economic burden, and negative impacts on patients' quality of life. Current therapeutic options with local traditional pharmaceutical formulations are largely focused on controlling symptoms, and only few agents are available for treatment. Several local supportive and palliative agents are used for the prevention of OM; however, a standard treatment for the disease has not been confirmed yet. The efficacy of treatment could be improved through the introduction of new medical agents with updated dosage forms that can enhance and optimize local drug delivery and create greater therapeutic effects with fewer side effects. The focus of this review was to provide clear and direct information about the currently available topical therapeutic agents in clinical practice used to cure and/or reduce the incidence of ulcerative symptoms of OM, excluding the associated pain and other coexisting complications such as bacterial and fungal infections. The review also provides recent evidences regarding agents that could be used as promising novel therapies in updated local delivering systems. This will support further encouraging options and approaches for the management of OM and will improve compliance that could be translated in better disease control and survival.